Innovative design of traditional patterns and exploration of cultural diversity symbiosis model in the context of digitalization - Wang, Youjian; Sheng, Muling; Ghani, Dahlan Abdul (Edelweiss Applied Science and Technology, 2025)
This paper takes the innovative design of traditional patterns as the research object, exploring the application of digital technology in the cultural diversity symbiosis model and its implementation path. First, traditional patterns are collected and digitized; pattern samples are extracted from folk art, historical documents, and intangible cultural heritage works, and structured storage is performed through image recognition and vectorization technology. Secondly, combined with the Generative Adversarial Network (GAN), the traditional patterns are transferred and reconstructed to generate innovative design solutions to ensure the continuity of their cultural elements. Then, the generated patterns are applied to a variety of design scenarios, including clothing, architectural decoration, and digital media design, through parametric design technology, and feedback data is collected using a user participatory design platform. Finally, based on the theory of multicultural symbiosis, the correlation between traditional patterns and modern design styles is established, and their adaptability and symbiosis in different cultural contexts are analyzed. The results show that the patterns generated based on GAN have a high innovation score. Digital technology can effectively promote the innovative design of traditional patterns. At the same time, it can realize the integration of tradition and modernity through the cultural diversity symbiosis model, providing a new path for the inheritance and development of intangible cultural heritage.